Cyanamide-modified iron (III) oxide photocatalysts for degradation of phenol in the presence of urea and formaldehyde - Nur Azmina Roslan,; Lintang, Hendrik O.; Leny Yuliati, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Cyanamide as the source of carbon and nitrogen was used to modify iron(III) oxide (Fe2O3) photocatalyst. While X-ray diffraction (XRD) patterns confirmed that the cyanamide-modified Fe2O3 photocatalysts have comparable crystallinity to that of the unmodified Fe2O3, the diffuse reflectance ultraviolet-visible (DR UV-vis) spectra obviously showed additional light absorption around 500-800 nm on the cyanamide-modified Fe2O3, resulting in a better absorption capability under visible light irradiation. The presence of cyanamide modifier decreased the fluorescence emission intensity of Fe2O3, implying the reduced electron-hole recombination on the Fe2O3 and/or blocked emission sites by the modifier. The presence of carbon and nitrogen on the modified Fe2O3 photocatalysts was confirmed by the elemental analyzer. Photocatalytic activities of Fe2O3 and cyanamide-modified Fe2O3 were then evaluated for degradation of phenol under UV and visible light irradiation. Modification of Fe2O3 with cyanamide significantly improved the degradation of phenol from 30 to 75% under UV light irradiation and from 0 to 80% under visible light irradiation. Photocatalytic degradation of phenol was also investigated in the presence of urea or formaldehyde or both urea and formaldehyde. Even though the percentage of phenol degradation decreased in the presence of other pollutants, it was demonstrated that cyanamide modified iron(III) oxide photocatalysts still gave good activity towards degradation of phenol even in the presence of other organic pollutants.